Character Education Values in Short Stories in Indonesian Textbooks for Class XI SMA - Riska, Riska (UIR Press, 2024)
This research is motivated by a collection of short stories contained in the Indonesian Class as an interesting and enjoyable literary learning material. The aim of this research is to describe, analyze and interpret the value of character education in short stories in Indonesian language textbooks for Class XI SMA. The theory used in this research is about the values ​​of character education according to Hasanuddin WS. The data source used is the Indonesian language textbook for Class XI SMA which contains a collection of short stories. The method used is descriptive analysis method. This research approach is a qualitative approach. The type of research used is library research. The results of the research can be concluded that there is character education value in Short Stories in Indonesian Language Textbooks for Class XI SMA. The research results show that the value of character education in aspects of faith and devotion is characterized by the behavior and attitudes of characters who believe in God's power. The aspect of honesty is characterized by the attitude and behavior of a character who can take responsibility for the character's words and behavior. The intelligence aspect can be characterized by the character's attitudes and behavior, being able to find solutions, think logically and think forward. The toughness aspect is characterized by the character's behavior of working hard and maintaining personal safety and health. The caring aspect is characterized by the character's behavior that obeys the norms and likes to help.